The roles of coaches, peers, and parents in athletes' basic psychological needs: A mixed-studies review. Issue 4 (August 2019) - Chu, Tsz Lun (Alan); Zhang, Tao
The purposes of this mixed-studies review were to summarize (a) the social environments created by coaches, peers, and parents concurrently, (b) the relative influence of social agents in youth athletes' psychological needs, and (c) the emerging research gaps for future research in and practical implications for youth sport. Literature was searched in six databases, resulting in 20 final studies with 2851 participants. These studies were reviewed and synthesized based on the theoretical frameworks, research design, participants and sports, associations between social environments and psychological needs, data analyses, results, and limitations. Results suggest that coaches, peers, and parents serve different roles in athletes' psychological needs. Coaches are the most important social agent in influencing autonomy, while peers are the most important social agent in influencing competence and relatedness. Parental influence is the least influential but also least studied in current literature. More research, particularly studies that use mixed methods or longitudinal design across developmental periods, is needed to examine the relative influence of all three social agents in youth sport contexts.